Secluding few lines on physiological interactions triggered by reducers - Islam, Muhammad Torequl (International Journal of Medicine, 2017)
Nowadays, we are very much concerned about the physiological contributions of oxidative species (e.g. - free radicals, reactive species). These include reactive oxygen/nitrogen species (ROS/RNS), vastly under continuous study in the medical concerns, emphasized on normal physiological as well as pathophysiological conditions. Being oxidizer, they have enforced us to search substances or conditions capability to counteract them, called the reducers. Doubtless, redox reaction has numerous roles in a biological system; despite we badly count the effects of ROS. This paper depicts some important interactions related to the reduction effects on the biological systems.